Raiders of the lost heart [large type] - Segura, Jo (Thorndike Press large print top shelf., 2024)
"Rival archaeologists must team up on a secret Aztec expedition, or it could leave their careers--and hearts--in ruins. Archaeologist Dr. Socorro "Corrie" Mejía has a bone to pick. Literally. It's been Corrie's life goal to lead an expedition deep into the Mexican jungle in search of the long-lost remains of her ancestor, Chimalli, an ancient warrior of the Aztec empire. But when she is invited to join an all-expenses-paid dig to do just that, Corrie is sure it's too good to be true... and she's right. As the world-renowned expert on Chimalli, by rights Corrie should be leading the expedition, not sharing the glory with her disgustingly handsome nemesis. But Dr. Ford Matthews has been finding new ways to best her since they were in grad school. Ford certainly isn't thrilled either--with everything going on in his life right now, the last thing he needs is a reminder of their rocky past. But as the dig begins, it becomes clear they'll need to work together when they realize a thief is lurking around their campsite, forcing the pair to keep their discoveries--and lingering attraction--under wraps. With money-hungry artifact smugglers, the Mexican authorities, and the lies between them closing in, there's only one way this all ends--explosively"--